Co‐creation of a student‐implemented allied health service in a First Nations remote community of East Arnhem Land, Australia. (15th November 2022) - Barker, Ruth; Witt, Susan; Bird, Katrina; Stothers, Kylie; Armstrong, Emily; Yunupingu, Murphy Dhayirra; Marika, Eunice Djerrkŋu; Brown, Louise; Moore, Renae; Campbell, Narelle
Abstract: Objectives: To co‐create a culturally responsive student‐implemented allied health service in a First Nations remote community and to determine the feasibility and acceptability of the service. Design: Co‐creation involved a pragmatic iterative process, based on participatory action research approaches. Feasibility and acceptability were determined using a mixed‐method pre/postdesign. Setting: The service was in Nhulunbuy, Yirrkala and surrounding remote First Nations communities of East Arnhem Land, Northern Territory, Australia. Participants: Co‐creation of the service was facilitated by the Northern Australia Research Network, guided by Indigenous Allied Health Australia leadership, with East Arnhem local community organisations and community members. Co‐creation of the day‐to‐day service model involved local cultural consultants, service users and their families, staff of community organisations, students, supervisors, placement coordinators and a site administrator. Findings: A reciprocal learning service model was co‐created in which culturally responsive practice was embedded. The service was feasible and acceptable: it was delivered as intended; resources were adequate; the service management system was workable; and the service was acceptable. Health outcome measures, however, were not appropriate to demonstrate impact, particularly through the lens of the people of East Arnhem. Recommendations for the service included: continuing the reciprocal learning service model in the long term; expanding to include all age groups; and connecting with visiting and community‐based services. Conclusion: The co‐created service was feasible and acceptable. To demonstrate the impact of the service, measures of health service impact that are important to First Nations people living in remote communities of northern Australia are required.